2015
DOI: 10.1016/j.bios.2015.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Impedimetric cell-based biosensor for real-time monitoring of cytopathic effects induced by dengue viruses

Abstract: We describe an impedimetric cell-based biosensor constructed from poly-l-lysine (PLL)-modified screen-printed carbon electrode for real-time monitoring of dengue virus (DENV) infection of surface-immobilized baby hamster kidney (BHK-21) fibroblast cells. Cytopathic effects (CPE) induced by DENV-2 New Guinea C strain (including degenerative morphological changes, detachment, membrane degradation and death of host cells), were reflected by drastic decrease in impedance signal response detected as early as ~30 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…ECIS instruments record impedance signals at a wide range of frequencies from 10 to 10 5 Hz. First of all, we determined the optimal frequency to analyze our impedance patterns using the Bode diagram ( 25 ), which is a visualization of the impedance over different frequencies at a time point of choice. By looking at the Bode diagram at 100 h postseeding (or 76 hpi, when impedance of infected cells at multiplicity of infection [MOI] 1 or MOI 0.1 had dropped to baseline level), we can identify the frequency that leads to the largest observed impedance difference between uninfected and infected cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ECIS instruments record impedance signals at a wide range of frequencies from 10 to 10 5 Hz. First of all, we determined the optimal frequency to analyze our impedance patterns using the Bode diagram ( 25 ), which is a visualization of the impedance over different frequencies at a time point of choice. By looking at the Bode diagram at 100 h postseeding (or 76 hpi, when impedance of infected cells at multiplicity of infection [MOI] 1 or MOI 0.1 had dropped to baseline level), we can identify the frequency that leads to the largest observed impedance difference between uninfected and infected cells.…”
Section: Resultsmentioning
confidence: 99%
“…Fang et al used CEI to study CPE induced by West Nile virus and St. Louis encephalitis virus and to quantify the protecting role of neutralizing antibodies ( 17 ). Cheng et al determined that DENV-induced CPE was observed earlier with CEI than with conventional microscopy ( 25 ). However, to our best knowledge, the consequences of ZIKV infection on cellular impedance and the evaluation of ZIKV inhibitors have never been studied using CEI.…”
Section: Introductionmentioning
confidence: 99%
“…The LbL coating of eukaryotic cells can protect them against the surrounding medium in biosensors. Thus, the cells can be used for applications such as the detection of hormones ,,,− (Figure a). A hormone detection system can identify xenoestrogens that cause mammalian cell disturbances .…”
Section: Applicationsmentioning
confidence: 99%
“…98 Cell-based biosensors use the physiologic response of whole cells to detect biologically active compounds. 99 Their potential usage includes the testing of biological effects in drug discovery, 100 assays in clinical diagnostics, 101 basic medical research, 102 and environmental monitoring for toxins and other hazardous chemicals. [103][104][105] Cellbased biosensors allowed the introduction and continuous optimization of phenotypical assays, with the latest approaches focusing on the realistic enhancement of the cellular biological relevance.…”
Section: Phenotypic Assaysmentioning
confidence: 99%